Metabolic measurements in classic and skating cross country simulated competition - de Angelis, M.; Faina, M.; Schena, F.; Trozzi, V.; Campaci, R.; Petrini, C. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts)
Introduction: The aim of this study was to investigate some physiological responses of athletes of both genders of cross-country skiing during two simulated short competitions in both the techniques, Skating (S) and Classic (C). Methods: Eight athletes (4 males, 4 females) of the Italian B national team [age: 22.3 (1.7) and 23.5 (4.19) ys; % fat: 7.9 (0.7) and 15.8 (2.6); V`O2max (at 1000m asl): 65.5 (2.8) and 56 (3.1) ml/kg/min] performed twice, with the two different techniques applied in a cross-over design, a simulated competition (9 km for males and 6 km for females) on a 3 km ring at an altitude of 1350m. In order to measure the real maximal blood lactate determined by the main steep slope, the athletes performed also, in a cross-over design, two partial competitions, interrupted on the top of the slope for the measurements of the increasing lactate. All the tests were conducted with a one day recovery in between. During each test heart rate (HR) and oxygen consumption (V`O2) on breath-by-breath basis were measured, by telemetric metabolimeter (K4b2, Cosmed, Italy). Average V`O2 (V`O2av) and V`O2peak (V`O2pk), expressed as % of V`O2max, as well as the rate of V`O2 increase at the beginning of the race (Mean Response Time - MRT) were calculated. Blood lactate concentration (BL) was measured (Lactate Pro, Arkray, Japan): a) just before the start; b) at each passage on the top of the main slope (1.8 km after the start); c) during the recovery after the interrupted competition; d) at the end of each lap; e) at the end of the test and during recovery (2°, 4°, 6°, 12° min). Maximal (BLmax) and Average (BLav) BL were expressed as net values by subtracting the basal value. Results: Males were much faster (22%) than females in climbing the slope, and not so much (8%) in the flatter part. The difference in total average speed between the faster males and the slower females was larger (40%) in C than in S. S was faster than C in both genders, but females showed a larger difference between the two techniques in climbing the slope (13%), compared to the flat part (7%), while males showed an opposite trend, with the larger difference in the flat part (13% vs 5%). After the interrupted competition, the highest BL net value, reached on average at the 2° min of recovery, was higher in C than S in males (7.8 vs 6.8 mM), but almost identical in the two techniques in females (8.3 vs 8.1 mM). Females showed also a higher BLmax than males (11.3 mM vs 8.6 mM) in the complete competitions. Most of the BL increase was detected just after the first slope (7.2 mM in females and 5.7 mM in males) but the BLmax was normally reached at the end of the competition. Like in the interrupted competition, males showed higher BLmax (about 1.7mM) in C than in S, while almost no BLmax difference was found in females. Despite the BL values, females showed higher V`O2av and V`O2pk in C than in S, while males showed higher V`O2av in S than in C. MRT was faster in S than in C both in males (-7s) and females (-5s). It was also faster (-5s) in males than in females. Neither the differences and the correlations were found to be statistically significant. However, not taking into account the skiing technique, the highest correlation indexes were found in the following relationships: MRT vs Total race time (R2=0.58 in males and 0.35 in females); MRT vs BLmax in males (R2=0.34); MRT vs BLav (R2=0.32 in females and 0.35 in males). Discussion/Conclusions: Females are slower than males mainly in climbing the slope and in C technique, even if they showed in C an higher V`O2av than in S. This could suggest that (besides to have more body fat than males) females are weaker than males; this has also been shown to increase energy cost of skiing. A technical analysis could probably help to understand why the main difference between S and C was found in the flat part and in climbing the slope, for males and females respectively. Technical differences with a different muscles recruitment, as well as a different aerobic and anaerobic involvement during the performance, could also explain the opposite behaviour of V`O2 and BL in males and females. The good, even if not significant, relationship between MRT and total time confirms that aerobic metabolism is a limiting factor of performance in cross-country skiing, but above all it suggests that the capability to quickly activate it can help in the whole race, saving some components of the anaerobic metabolism at every sudden change of intensity. This saving could permit a bigger increase in power by the anaerobic metabolism.